2006
DOI: 10.1084/jem.20060401
|View full text |Cite
|
Sign up to set email alerts
|

Properties regulating the nature of the plasmacytoid dendritic cell response to Toll-like receptor 9 activation

Abstract: Human plasmacytoid dendritic cells (PDCs) can produce interferon (IFN)-α and/or mature and participate in the adaptive immune response. Three classes of CpG oligonucleotide ligands for Toll-like receptor (TLR)9 can be distinguished by different sequence motifs and different abilities to stimulate IFN-α production and maturation of PDCs. We show that the nature of the PDC response is determined by the higher order structure and endosomal location of the CpG oligonucleotide. Activation of TLR9 by the multimeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
360
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(382 citation statements)
references
References 39 publications
13
360
4
5
Order By: Relevance
“…There is mounting evidence that both subcellular localization and endosomal pH can influence the ability of endosomal TLRs to signal. For example, the TLR9 response to exogenous CpG DNA is dependent on specific endosomal localization and acidification (Guiducci et al , 2006; Yao et al , 2009; Okuya et al , 2010; Hazeki et al , 2013; Duhamel et al , 2016). Sasai et al (2010) showed TLR9 signaling leading to activation of type I IFN but not pro‐inflammatory cytokine genes require TLR9 trafficking from endosomes to a specialized lysosome‐related organelle dependent on AP‐3.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that both subcellular localization and endosomal pH can influence the ability of endosomal TLRs to signal. For example, the TLR9 response to exogenous CpG DNA is dependent on specific endosomal localization and acidification (Guiducci et al , 2006; Yao et al , 2009; Okuya et al , 2010; Hazeki et al , 2013; Duhamel et al , 2016). Sasai et al (2010) showed TLR9 signaling leading to activation of type I IFN but not pro‐inflammatory cytokine genes require TLR9 trafficking from endosomes to a specialized lysosome‐related organelle dependent on AP‐3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that type B CpG ODNs predominantly activate pDCs in a manner that results in phenotypic changes and pro-inflammatory cytokine production, as well as weak induction of type I IFN responses [53]. The functional activity of type B CpG ODNs is attributed to their localization to lysosome-associated membrane protein 1-positive endosomes, while activation of TLR9 by type A CpG ODNs occurs in transferrin receptor-positive endosomes [54].…”
Section: Discussionmentioning
confidence: 99%
“…12 The distinct biology of each class is thought to be related to their differential capacity to form secondary or higher-order structures and localize to discrete intracellular compartments. 16 The A-class have phosphodiester/phosphorothioate chimeric backbones, form complex tertiary structures, and are poor at activating B cells but potent for inducing IFN-␣ production from pDCs. B-class CpG ODNs have a whole phosphorothioate backbone, do not form secondary or tertiary structures, and are potent B cell activators but weak for inducing pDCs to produce IFN-␣.…”
Section: Discussionmentioning
confidence: 99%